Romansko-slovanske jezikovne interference - Skubic, Mitja (Slavistična revija, 2001)
The article attempts to determinate deviation from the current norm in Romance languages in three syntactic features, i.e., in the sequence of tenses, the use of double negation, and case forms of the reflexive pronouns. These deviations are examined in Romanian and the areas of contact between Romance and Slavic, which are currently (besides Romania) only in Istria and the Julian March. In the opposite direction the author finds the same syntactic calques in Slovene in these contact or linguistically mixed area.
Keywords: linguistics; lingvistika; oziralni zaimek; romanski jeziki; romunščina; sintaksa; Slavic languages; slovanski jeziki; Slovene; slovenščina; sosledje časov